Prolonged physical isolation, agonistic behaviour, and human resilience in pandemic times - Marsico, Giuseppina; Russo, Claudio (Frontiers in Public Health, 2025)
With the purpose of enhancing a comprehensive approach to healthcare, public health initiatives have moved from managing the pandemic response towards an increased understanding of the sequelae, including but not limited to mental health issues triggered by societal limitations and precautionary measures. The long-term effects of the COVID-19 pandemic lie in the health system’s capacity to promote a renewed sense of healthy communities, strengthen individual resilience, and mitigate environmental stressors in the future. Under these terms, the pandemic breakdown has been discussed in relation to the public health crisis and physical isolation resulting from SARS-CoV-2 disease.